Impact of milk thistle (Silybum marianum) on the mycotoxin caused redox-homeostasis imbalance of ducks liver. (November 2020) - Egresi, Anna; Süle, Krisztina; Szentmihályi, Klára; Blázovics, Anna; Fehér, Erzsébet; Hagymási, Krisztina; Fébel, Hedvig
Abstract: The Fusarium mycotoxins deoxynivalenol (DON) and zearalenone (ZEA) frequently contaminate grain crops, especially maize, the basis of poultry's feed. Mycotoxins enter the food chain and induce pathological changes in edible tissues. Milk thistle (Silybum marianum) has been used for the treatment of liver disease in humans because of its antioxidant and hepatoprotective effects, but its utility in veterinary use is poorly examined. To investigate possible protective properties against mycotoxin caused oxidative stress in poultry, pressed form of milk thistle seed (0.5%) was tested in white, female, Hungarian ducks over a feeding period of 47 days. Ducks were separated into 3 groups. The first group was fed with normal diet. The second group was fed with normal diet contaminated with DON (4.9 mg/kg) and ZEA (0.66 mg/kg). The third group received mycotoxin contaminated feed with milk thistle supplementation. Histological examination, markers of the redox status and metal element concentration measurements were carried out. The results showed alterations in the histological examination and in the redox homeostasis markers as a short-term effect by strengthening the antioxidant system. Acute exposure of mycotoxins caused an oxidative stress, which induced an effective antioxidant defensive response of the organism indicated by the free sulfhydryl group content (from 0.72 ± 0.06 to 0.77 ± 0.11) and the reducing power (0.49 ± 0.06 to 0.52 ± 0.08) elevation. The short-term free radical injury may be compensated by the liver resulting in decreased lipid peroxidation markers (malondialdehyde concentration: from 16.86 ± 0.49 to 0.94 ± 0.15, conjugated diene concentration: from 0.21 ± 0.07 to 0.17 ± 0.03). Silymarin further strengthtened the antioxidant defense by the elevation of sulfhydryl groups concentration and reducing power property resulted in decreased total scavenger capacity. However the concentration of lipid peroxidation markers were further elevated by the used antioxidant treatment (MDA: 5.2 ± 0.35, DC: 0.26 ± 0.08). In conclusion, the mycotoxin-contamination activated effectively the antioxidant system. The milk thistle supplementation has cytoprotective effects according to the histological findings, activated the antioxidant system, however the elevation of lipid peroxidation products need further explanation. Graphical abstract: Image 1 Highlights: Mycotoxin caused oxidative stress induces an antioxidant defence of the organism. The ROS injury was compensated, resulting in decreased lipid peroxidation markers. Mycotoxins caused changes in metal element homeostasis. Metal element changes were not protected by milk thistle supplementation. Milk thistle supplementation can enhance the antioxidative defence in duck's liver.